Enhancing Fuel Oil from Polyethylene Waste: A Comparative Study of Catalyst Efficiency in Thermal Pyrolysis - Dhaniswara, Trisna Kumala; Juliasti, Sri Rachmania; Mahfud, Mahfud (Eksergi, 2025)
The growing accumulation of polyethylene (PE) plastic waste poses a significant environmental challenge, necessitating effective recycling and waste management solutions. Thermal pyrolysis has emerged as a promising method for converting plastic waste into valuable hydrocarbons. This study presents a comparative analysis of catalyst efficiency in the thermal pyrolysis of PE waste, with a focus on maximizing product yield and optimizing chemical composition. Various catalysts were evaluated to assess their impact on the degradation process, product distribution, and overall conversion efficiency. The research utilized 100 grams of PE waste in the form of 2 cm pellets. The catalysts tested—activated carbon, HZSM-5, and low-rank coal (LRC)—were each added at 10% of the plastic's weight. The experiments were conducted under varying conditions of time (30, 60, 90, 120, 150, and 180 minutes) and temperature (350, 450, 550, and 650°C). The thermal pyrolysis setup included an integrated furnace with glass column fractionation and four trays for collecting liquid pyrolysis products. Key parameters such as total yield, °API and calorific value were analyzed and compared to those of conventional fuel oil. The results demonstrated that the LRC catalyst outperformed both activated carbon and HZSM-5, achieving a yield of 61.10% at 650°C for 180 minutes. The pyrolysis product obtained using the LRC catalyst exhibited properties—such as °API and calorific value—comparable to those of conventional gasoline. This study highlights the potential of catalytic pyrolysis in managing plastic waste effectively, offering a viable approach to reducing plastic pollution while producing valuable hydrocarbon products. The findings underscore the importance of catalyst selection in optimizing pyrolysis outcomes, providing valuable insights for sustainable plastic waste management